Conclusion of an Agreement under the General and Special Administrative Penal Procedural Order - Nikolova, Rayna (Law Journal of New Bulgarian University, 2024)
The study examines the agreement concluded under the Administrative Violations and Sanctions Act and some special administrative laws as a procedural institution of administrative penal procedural law. It provides a doctrinal definition of this legal concept. It examines the legal nature of the agreement concluded under the general administrative penal procedural order. It discusses the conclusion of an agreement to terminate the administrative penal proceedings on a special basis. It conducts a comparative analysis of the procedures for concluding agreements under different procedural laws and the legal nature of the agreement as a legal act.